KAJIAN SEMANTIK PERISTILAHAN PENGOBATAN TRADISIONAL â€œBEPIARAOâ€ PADA MASYARAKAT DAYAK KETUNGAU SESAT - Siska, Margareta; Simanjuntak, Hotma; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTraditional medicine "bepiarao" is a traditional treatment of the Dayak Ketungau Sesat society whose healing is carried out by Manang (Shaman). This research deals with the field of linguistics, especially regarding the semantic field which discusses the meaning of words. Writing the problem in this study was the Semantic Study of Traditional Medicine "Bepiarao" in the Ketungau Sesat Dayak Society, which is limited by sub problems regarding the form of terminology, lexical meanings, cultural meanings, and the implications for learning in school. The method used in this research was descriptive method with a qualitative research form. The data source of this research was the Ketungau Sesat Dayak language spoken by the informant. The data of this study were the terminology of "bepiarao" traditional medicine in the Ketungau Sesat Dayak society. Data collection techniques used in this study was upfront techniques, note taking techniques, and record techniques. This research data collection tool was a recording sheet in the form of question instruments and documentation tools. The results obtained 74 data that consist of 13 tools, 36 materials, 7 cultural objects, 5 diseases, 3 subject, 3 stages, 1 taboo, and 7 units in terms of verbs, nouns, prefixes, compound words and the most dominant is noun. All data have lexical meaning, and some have cultural meaning. The implication of learning in schools is in the form of description text and plans for implementing the description text learning. Keywords: Dayak Ketungau Sesat, Terminology, Traditional Medicine ?bepiarao?